Wind speed and soil properties drive the height-diameter allometric pattern of island plants - Chengfeng Yang; Renfu Liao; Shengzhuo Huang; Yikang Cheng; Shurong Zhou (Frontiers in Plant Science)
IntroductionIsland ecosystems, due to their geographical isolation and unique environmental conditions, often serve as natural laboratories for ecological research and are also sensitive to global climate change and biodiversity loss. The allometric relationship between plant height-diameter reflects the adaptive growth strategy of plants under different environmental conditions, particularly in response to biomechanical constraints (e.g., wind resistance) and resource availability. This study aims to explore the key driving factors of the height-diameter allometry of island plants, focusing on how island area, soil properties, and climatic factors (e.g., wind speed, temperature, and precipitation) affect plant growth strategy.MethodsWe analyzed plant data from 20 tropical islands, using SMA regression to calculate the allometric exponent and intercept for each island’s plants, and evaluated the effects of island area, soil properties, and climatic factors (wind speed, temperature, and precipitation) on the height-diameter allometric relationship.ResultsThe results show that island area has no significant effect on plant allometry, while climatic factors, particularly wind speed, and soil properties significantly influence the allometric exponent and intercept, respectively. Specifically, wind speed is the primary driver of the height-diameter allometric exponent, regulating plant growth proportions through mechanical stress and canopy limitation. In contrast, soil properties predominantly govern changes in the allometric intercept, reflecting their critical role in determining baseline growth conditions, such as resource allocation and initial morphological adaptation. The effects of temperature and precipitation are relatively weak, likely due to the buffering effects of the tropical climate and marine moisture supplementation.DiscussionOverall, this study highlights the key roles of wind speed and soil in shaping the allometry of island plants, providing new insights into the adaptive strategies of island plants under resource limitations and climatic pressures, as well as offering important scientific evidence for island ecological conservation and restoration.